IDENTITY NEGOTIATION, COGNITIVE PROCESSING, AND DIGITAL DOMINANCE: A SOCIO-PSYCHOLINGUISTIC ANALYSIS OF ENGLISH LANGUAGE USE AMONG INDONESIAN YOUTH - Bahagia Saragih; Barli Kifli; Noela Ashyera Manik; Yohana Clara Elisabeth Simbolon; Revalen Andryany Br Ambarita; Ririn Prinita Sihotang; Trisia Inggreya Saragih; Yeane Celcelia Simanjuntak (STKIP Subang, 2026)
The proliferation of English across Indonesian digital and social land-scapes has generated complex sociolinguistic phenomena among young speakers, encompassing code-switching practices, accent ideol-ogy conflicts, and evolving cognitive patterns. This study investigates the intersections of identity negotiation, cognitive processing, and the in-fluence of digital media on English language use among a group of In-donesian senior high school students aged 16-18 in Medan. A mixed-methods design was employed, combining a five-item Likert-scale sur-vey administered to 15 respondents with in-depth qualitative interviews and open-ended responses. Quantitative data were analyzed descrip-tively, while qualitative findings were subjected to thematic coding and socio-psycholinguistic interpretation. Findings reveal that code-switching commands the highest agreement (Mean = 4.00), functioning as both a communicative tool and a vehicle for social identity construction. Confi-dence in formal English use stands at a moderate-high level (Mean = 3.47), while the cognitive shift toward thinking in English remains devel-opmental (Mean = 3.20). Accent ideology produces a near-equal but emotionally charged divide: 53.33% favor native-like pronunciation while 46.67% advocate for localized accent retention. Social media emerges as the primary driver of English lexical acquisition (Mean = 3.60), em-bedding slang terms such as literally, cringe, and slay into everyday dis-course. The findings contribute to socio-psycholinguistic scholarship by demonstrating that English use among these young learners is not merely a communicative act but a dynamic process of identity perfor-mance, cognitive becoming, and resistance to linguistic normativity in the digital era.